Choix thérapeutiques des hypertendus et diabétiques en milieu rural : Une étude mixte dans deux zones de santé de l’Est de la République Démocratique du Congo - Aimé C. Mwana-wabene; Samuel M. Lwamushi; Christian M. Eboma; Pacifique M-B. Lyabayungu; Bonfils Cheruga; Hermès Karemere; Albert T. Mwembo; Ghislain B. Balaluka; Faustin C. Mukalenge (African Journal of Primary Health Care & Family Medicine, 2022)
Therapeutic choices of hypertensive and diabetics in rural areas: A mixed study in two health zones in the East of the Democratic Republic of Congo.